(untitled) (Nepal Journal of Environmental Science, 2023)
Smooth-coated Otter (SCO), a top predator and health indicator of the aquatic ecosystem is included as vulnerable on the IUCN red list and listed in Appendix I. Geruwa-Khaurahi River (GKR) was observed to determine the habitat status of SCO between Bardiya National Park (BNP) and Khata Corridor (KC), and to evaluate factors affecting the SCO habitat, data on habitat parameters and SCO signs were collected in each transect of 500 m. Principal component analysis was used for the most probable habitat parameter selection. An SCO group of eight was observed at Lalmati on the broad, shallow, and fast-flowing GKR with a sandy island and a flat stone bank with a vast escape distance. All signs were found on the sandy shoreline of the riverine forest with nearby tall Saccharum coverage over a narrow escape cover with a gentle bank slope. Diversions of water from the Geruwa River to the narrow and shallow Khaurahi River resulted in fast-flowing water where SCO pugmarks were found abundant. But at KC, human disturbances, over-fishing, river mining, and infrastructures have made the river unsuitable for SCO. SCO preferred dense riverine forests where the gentle riverbank has sand and/or tall Saccharum in between a narrow escape distance. Also, the narrow river with shallow depth and slow flow of good water quality was preferred by SCO. Lastly, with minimal human disturbance, further study on feeding ecology and population dynamics is requisite to conserve the suitable habitat of the SCO.